TRANSITIVITY ANALYSIS REPRESENTING HONG KONG PROTEST 2019 IN THE GUARDIAN NEWS ARTICLE - Rahmasari, Shafira (Journal of Language and Literature, 2020)
News is one of a medium to give new and recent information regarding particular event including the person that is involved that is published by news publishers. One of the leading publishers in The United Kingdom is The Guardian. The Guardian reported an international news which was the activists and pro-democracy figures arrested on Hong Kong protest 2019 that was published in August, 30 2019. The paper attempts to find out the transitivity process to see how the protest is represented. It applied transitivity as the theoretical framework and discourse analysis as the approach. Based on the analysis, material process appears as the most frequent process followed by verbal, mental, and relational process. It is seen that the authorities and the government have the authority to control the protest including the activists and the activists are powerless during the arrested. Besides, the pro-democracy figures still have a room to express their opinion while the activists give their statement after being released seen through the verbal process. Relational process and mental process remark that the activists are prominent figures through the protest. In addition, circumstances are used to give detail information regarding the process.